2011
DOI: 10.1037/a0021072
|View full text |Cite
|
Sign up to set email alerts
|

Stability and change in intelligence from age 11 to ages 70, 79, and 87: The Lothian Birth Cohorts of 1921 and 1936.

Abstract: Investigating the predictors of age-related cognitive change is a research priority. However, it is first necessary to discover the long-term stability of measures of cognitive ability because prior cognitive ability level might contribute to the amount of cognitive change experienced within old age. These two issues were examined in the Lothian Birth Cohorts of 1921 and 1936. Cognitive ability data were available from age 11 years when the participants completed the Moray House Test No. 12 (MHT). The Lothian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
129
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(144 citation statements)
references
References 41 publications
11
129
1
3
Order By: Relevance
“…The largest effect size obtained for serial digits confirms previous findings for substantial improvement in working memory with age [2]. Based on evidence associating age-related changes in specific cognitive tasks and changes in the neural substrates in the prefrontal lobe in childhood and adolescence, working memory together with other executive functions has been documented as influenced by maturation [3,8]. The additional two large effect sizes found for form completion and localization -two visuospatial tasks, are in accord with previous suggestions for agerelated maturation for executive functions [47].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The largest effect size obtained for serial digits confirms previous findings for substantial improvement in working memory with age [2]. Based on evidence associating age-related changes in specific cognitive tasks and changes in the neural substrates in the prefrontal lobe in childhood and adolescence, working memory together with other executive functions has been documented as influenced by maturation [3,8]. The additional two large effect sizes found for form completion and localization -two visuospatial tasks, are in accord with previous suggestions for agerelated maturation for executive functions [47].…”
Section: Discussionsupporting
confidence: 71%
“…Gur et al [2] found age-related effects on performance across all cognitive domains that have been examined; however, some domains demonstrated larger age differences than others. For example, the largest age difference in performance was found for two executive domains: working memory and attention, which had received support from earlier publications [3], whereas, for mental flexibility and abstraction small to moderate effect sizes for improvement with age were found. Other findings regarding visuospatial performance have also documented improvement with age.…”
Section: Introductionmentioning
confidence: 69%
“…Reasons for not attending included withdrawal (n = 16 at age 83; n = 4 at age 87), inability or refusal to participate (n = 80 at age 83; n = 42 at age 87), having moved away (n = 13 at age 83; n = 4 at age 87), exclusion due to dementia or memory problems (n = 3 at age 87) and death (n = 10 at age 83; n = 8 at age 87). 30,31 Of the total sample of 550 individuals, 229 had died during the course of the study. All participants lived independently in the community at baseline and most were in good general health.…”
Section: Study Populationmentioning
confidence: 99%
“…More recently the results regarding cognitive stability were replicated in the Lothian Birth Cohorts, which covered global intelligence between 11 and 70-87 years of age (38). Childhood global cognitive ability was the most powerful predictor of global cognitive ability in late life.…”
Section: Cognitive Stabilitymentioning
confidence: 50%